Unity 5 : creating the game environment - Lavieri, Edward D., Jr.; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Unity is an exciting and popular engine in the game industry. Throughout this course, you'll learn how to build a game consisting of a User Interface and explore more Unity game development concepts. This easy-to-follow course will help you quickly learn how to use Unity in a practical context, step-by-step, by making a real-world game project. This course will familiarize you with game project workflow and level design. You will learn to create and lay out the User Interface. This course will also walk you through scripting UI controls by testing and editing UI functionality. You will explore how to create a terrain, importing and using vegetation objects, and add a water feature to it. And then finally you'll work with textures."--Resource description page.
Presenter, Edward Lavieri.
Title from title screen (viewed February 15, 2017).
Date of publication from resource description page.
Keywords: Computer games -- Design; Computer games -- Programming; Video games -- Design; Video games -- Programming; Unity (Electronic resource); Electronic books